1992
DOI: 10.1203/00006450-199209000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Defense Mechanisms of Endothelial Cells and Renal Tubular Epithelial Cells In Vitro: Role of the Glutathione Redox Cycle and Catalase

Abstract: ABSTRACT. We recently demonstrated that endothelial cells are more susceptible than renal tubular epithelial cells to oxidant injury and that renal tubular epithelial cells with proximal tubular characteristics including porcine proximal tubular epithelial cells, opossum kidney proximal tubular epithelial cells, and normal human kidney cortical epithelial cells are more susceptible to oxidant injury than the distal nephron-derived Madin Darby canine kidney cell line. To determine the basis of this differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…Previous studies have indicated that catalase activity is high in alveolar pneumocytes and macrophages, and catalase inhibition significantly reduces H 2 O 2 consumption by these cells (Kinnula et al, 1992b;Pietarinen et al, 1995). On the other hand, endothelial cells appear to protect themselves by the glutathione redox cycle, but not by catalase (Schraufstätter et al, 1985;Andreoli et al, 1992;Kinnula et al, 1992c). To further examine which antioxidant enzyme mechanism plays a major role as a free radical scavenger in these cells, we inhibited catalase with ATZ or γ-GCS with BSO and measured oxidant generation in both intact unexposed cells and cells exposed to menadione.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that catalase activity is high in alveolar pneumocytes and macrophages, and catalase inhibition significantly reduces H 2 O 2 consumption by these cells (Kinnula et al, 1992b;Pietarinen et al, 1995). On the other hand, endothelial cells appear to protect themselves by the glutathione redox cycle, but not by catalase (Schraufstätter et al, 1985;Andreoli et al, 1992;Kinnula et al, 1992c). To further examine which antioxidant enzyme mechanism plays a major role as a free radical scavenger in these cells, we inhibited catalase with ATZ or γ-GCS with BSO and measured oxidant generation in both intact unexposed cells and cells exposed to menadione.…”
Section: Discussionmentioning
confidence: 99%
“…Such possibilities as altered glomerular hemodynamic response, impaired renal concentration of nephrotoxins, less tubular backleak, reduced cast formation, and an inherent resistance of regenerating cells, are all speculative (10,11). Resistance to injury is dictated, in part, by the presence of the appropriate defense mechanisms as exemplified by the relative susceptibility to oxidant injury in different parts of the nephron (21,22). Quite recently, Zager and colleagues have provided significant contributions indicating that the acquisition of resistance is influenced by the setting, in vivo vs in vitro, in which it is explored (23, 24); that an inherent resistance to injury resides in plasma membrane of proximal tubules harvested from kidneys previously conditioned in vivo by ischemia (25,26) or urinary tract obstruction (27); and, as emblematic of one of the few mechanistic explorations for acquired resistance, cellular resistance to ATP depletion is dependent on the disappearance/de-phosphorylation of a 130-kD tyrosine-phosphorylated protein/ protein complex (28).…”
Section: Introductionmentioning
confidence: 99%
“…Adenine nucleotide depletion and purine nucleoside and base accumulation are sensitive methods for the assessment of oxidant-related cell injury; LDH release is not as sensitive and reflects cell membrane damage (Hyslop et al, 1988;Andreoli et al, 1992;Kinnula et al, 1994). Our data on LDH release showed that asbestos fiber exposure results in cell membrane injury, and that the cell membrane damage was similar in amosite-and amosite +TNF-exposed cells.…”
Section: Discussionmentioning
confidence: 54%